Community of Helminth Parasites in Rita rita (Hamilton Buchanun) - Khanum, Hamida; Ferdows, Jakia; Farhana, Rima (Journal of Bio-Science, 2009)
Key words: Rita rita, helminthes, prevalence and intensity of parasites. DOI:10.3329/jbs.v16i0.3757 J. bio-sci. 16: 133-135, 2008